2022
DOI: 10.1158/1538-7445.sabcs21-ot1-11-02
|View full text |Cite
|
Sign up to set email alerts
|

Abstract OT1-11-02: A pragmatic, randomised, multicentre trial evaluating the dose timing (morning vs evening) of endocrine therapy and its effects on tolerability and compliance (REaCT-CHRONO Study)

Abstract: Background. Endocrine therapy (ET) is the mainstay treatment for hormonal receptor positive (HR+) breast cancer. ET non-compliance and non-persistence vary from 30 to 70% and are associated with reduced disease-free and overall survival. ET side effects are an important cause of non-adherence. In clinical practice, there are anecdotal reports that time of the day at which ET is taken may affect ET side effects and compliance. However, we are not aware of any high-quality studies supporting this practice. In ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“… 19 A pragmatic randomized trial comparing morning versus evening dosing of endocrine therapy for early breast cancer (REaCT-CHRONO Study) was presented at San Antonio breast cancer symposium in 2023 and found no difference in the effects of ET timings on ET intake compliance or quality of life. 26 …”
Section: Discussionmentioning
confidence: 99%
“… 19 A pragmatic randomized trial comparing morning versus evening dosing of endocrine therapy for early breast cancer (REaCT-CHRONO Study) was presented at San Antonio breast cancer symposium in 2023 and found no difference in the effects of ET timings on ET intake compliance or quality of life. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Between June 2021 and March 2022, 245 eligible patients were randomized (16). The results showed no significant difference in endocrine therapy toxicity and tolerability between the morning and evening timings of endocrine therapy (Table 1, Figure 1) (16).…”
Section: React-chrono (Pi: Marie-france Savard)mentioning
confidence: 98%
“…No prospective evidence exists for whether the time of day of administration affects endocrine side effects. The REaCT-CHRONO study randomized patients receiving adjuvant endocrine therapy to either morning or evening doses of endocrine therapy [ 15 ]. The primary endpoint was endocrine therapy toxicity and tolerability measured by the change in the total Functional Assessment of Cancer Therapy-Endocrine Subscale (FACT-ES) score from the baseline to 12 weeks following the beginning of ET.…”
Section: Review Of Recently Completed and Currently Accruing React St...mentioning
confidence: 99%
See 1 more Smart Citation